2002
DOI: 10.1074/jbc.m206334200
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Stability, and Aggregation of Paired Helical Filaments from Tau Protein and FTDP-17 Mutants Probed by Tryptophan Scanning Mutagenesis

Abstract: By using tryptophan scanning mutagenesis, we observed the kinetics and structure of the polymerization of tau into paired helical filaments (PHFs) independently of exogenous reporter dyes. The fluorescence exhibits pronounced blue shifts due to burial of the residue inside PHFs, depending on Trp position. The effect is greatest near the center of the repeat domain, showing that the packing is tightest near the ␤-structure inducing hexapeptide motifs. The tryptophan response allows measurement of PHF stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 52 publications
5
63
0
Order By: Relevance
“…Tau oligomerization could play a key role in either mechanism. For example, several authors have suggested that the FTDP-17 tau mutations causing amino acid substitutions lead to an increased probability of forming abnormal tau oligomers and then fibers (paired helical filaments/ neurofibrillary tangles) (46,47). Abnormal oligomerization, the gained function, could be a precursor state to assembly of the larger cytotoxic fibers.…”
Section: Molecular Mechanisms By Which Tauopathies May Results In Neurmentioning
confidence: 99%
“…Tau oligomerization could play a key role in either mechanism. For example, several authors have suggested that the FTDP-17 tau mutations causing amino acid substitutions lead to an increased probability of forming abnormal tau oligomers and then fibers (paired helical filaments/ neurofibrillary tangles) (46,47). Abnormal oligomerization, the gained function, could be a precursor state to assembly of the larger cytotoxic fibers.…”
Section: Molecular Mechanisms By Which Tauopathies May Results In Neurmentioning
confidence: 99%
“…PHF assembly appears to occur in stages (Friedhoff et al, 1998), and this noncross-linked, phosphorylated tau protein may represent a stage of PHF formation in which tau aggregates are unstable. When anionic inducing agents stimulate PHF formation in vitro, the stability of the tau aggregates and resistance to denaturation is low (Li et al, 2002). However, combining transglutaminase with tau in vitro results in stable, insoluble tau filaments (Dudek and Johnson, 1993;Appelt and Balin, 1997) that are biochemically similar to PHF from AD (Selkoe et al, 1982a).…”
Section: Discussionmentioning
confidence: 99%
“…The initial in vitro analyses of point-mutated tau proteins revealed relatively subtle reductions in MT-binding and assembly activities (5,(40)(41)(42). Many point-mutated proteins also increase tau fiber formation activity in vitro (29,41,43,44). The final important clue to tau action provided by the FTDP-17 mutations is that all of the mutations exhibit dominant rather than recessive phenotypes.…”
Section: Mechanistic Implications For Tau-mediated Neuronal Cell Deatmentioning
confidence: 99%